2003
DOI: 10.1161/01.cir.0000080894.51311.0a
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Distal Protection With a Filter-Based Catheter and a Balloon Occlusion and Aspiration System During Percutaneous Intervention of Diseased Saphenous Vein Aorto-Coronary Bypass Grafts

Abstract: for the FilterWire EX Randomized Evaluation (FIRE) InvestigatorsBackground-The high rate of periprocedural complications resulting from atherothrombotic embolization after percutaneous intervention in diseased saphenous vein grafts is reduced by distal microcirculatory protection using a balloon occlusion and aspiration system. Whether filter-based catheters, which offer the inherent advantages of maintained perfusion and ease of use, are as effective for this purpose has not been established. Methods and Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(89 citation statements)
references
References 19 publications
3
85
0
1
Order By: Relevance
“…Thus, treatment of SVG disease currently accounts for about 10% of all percutaneous coronary interventions (PCI) [12]. Since embolization of friable material was a main problem with percutaneous techniques, distal embolic protection [13, 14] and mechanical thrombectomy of large luminal thrombi [15, 16] were beneficial regarding short-term major adverse clinical events (MACE), but long-term outcome after PCI of SVG lesions remains poor, primarily due to the high incidence of restenosis and atherosclerotic disease progression [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, treatment of SVG disease currently accounts for about 10% of all percutaneous coronary interventions (PCI) [12]. Since embolization of friable material was a main problem with percutaneous techniques, distal embolic protection [13, 14] and mechanical thrombectomy of large luminal thrombi [15, 16] were beneficial regarding short-term major adverse clinical events (MACE), but long-term outcome after PCI of SVG lesions remains poor, primarily due to the high incidence of restenosis and atherosclerotic disease progression [17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…Use of the filterwire resulted in a median 3-minute increase in procedure time (median [IQR]) (16 [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] vs 13 [IQR 8-23], P = .06). After the procedure TIMI III flow was obtained in 94% of patients treated with distal protection compared with 87% who received conventional treatment (P = .03) ( Table 3).…”
Section: Procedural Results and Angiographic Outcomementioning
confidence: 99%
“…[10][11][12] Use of a filterwire system has improved PCI results of saphenous vein grafts. 13 Therefore, The Drug Elution and Distal Protection in ST-Elevation Myocardial Infarction (DEDICATION) trial was designed to evaluate the potential benefit of routine filterwire treatment in adjunctive to conventional PCI in patients with a STEMI presenting within 12 hours of symptom onset. 14 In the DEDICATION trial we observed a 10% increase in achieved TIMI flow 3 in the filterwire group, but there was no significant benefit with respect to ECG ST-segment resolution, which was the primary endpoint of the study.…”
Section: Introductionmentioning
confidence: 99%
“…4), providing equivalent results to the GuardWire TM device, while offering the advantage of maintained perfusion to the distal vessel segment during PTCA and stenting [29].…”
Section: Concepts and Strategiesmentioning
confidence: 99%